Reaction of mast cells to chronic stress during inflammatory stage of wound healing in rats - Makyeyeva, L. V.; Макєєва, Людмила Валеріївна (My University, 2021)
The aim of this research was to study the dynamics of the morphological and functional state of mast cells (MCs) in healthy and chronically stressed rats during inflammatory stage of wound healing.